Cats: Nature and Nurture - Andy Hirsch (First Second, 2019)
In Andy Hirsch's Science Comics: Cats, we meet feline friends from the tiniest kodkod to the biggest tiger, and find out what makes your neighborhood domestic cats so special. Equipped with teeth, claws, and camouflage to survive everywhere from deserts to mountaintops, how did these ferocious felines make the leap from predators to playmates... and are they even done leaping? Every volume of Science Comics offers a complete introduction to a particular topic$1 (Bdinosaurs, the solar system, robots, and more. Whether you're a fourth grader doing a natural science unit at school or a thirty year old with a secret passion for airplanes, these books are for you!s
Keywords: Narrative Non-Fiction -- Narrative Non-Fiction